2011
DOI: 10.1007/s00024-011-0297-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Approach in Investigating Volcano-Hydrothermal Systems: the Case Study of Vulcano (Aeolian Islands, Italy)

Abstract: Seismic activity, ground deformation, and soil and fumarole temperatures acquired during 2004-2007 at Vulcano (Aeolian Islands) are analysed and the time relations among the different time series are discussed. Changes in temperature of fumarolic gases took place during four ''anomalous'' periods () at the same time as an increasing number of volcano-seismic events. In particular, the temperatures at high temperature vents and at steam heated soil ranged in time from 180 to 440°C and from 20 to 90°C, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 47 publications
6
29
0
3
Order By: Relevance
“…In order to get a better overview of the fumarolic activity, we also used for comparison data from other instruments of the volcano perma nent network ( Fig. 3a): i) a rain gauge providing hourly measurements, located in open air at the harbor, about 1000 m from the PN tempera ture station (database Istituto Nazionale di Geofisica e Vulcanologia, Sezione di Palermo, courtesy of Paolo Madonia); ii) a seismic station maintained by the INGV from which the daily number of seismic events can be counted (Cannata et al, 2012); iii) a UV scanning DOAS MARK1 allowing daily estimations of the total SO 2 flux from the volcano (see an extended description in Vita et al, 2012); and iv) a WEST Systems CO 2 flux meter with an automated accumulation chamber providing daily estimate of the diffuse CO 2 flux at the summit area (see an extend ed description in Inguaggiato et al, 2012b) coupled with an open air thermometer. Note that the geochemical data were not corrected from the atmospheric conditions that may influence the observations (Viveiros et al, 2008), and that the reported seismic data represent the daily number of events and short lived interruptions may have caused some values underestimations.…”
Section: La Fossa DI Vulcanomentioning
confidence: 99%
“…In order to get a better overview of the fumarolic activity, we also used for comparison data from other instruments of the volcano perma nent network ( Fig. 3a): i) a rain gauge providing hourly measurements, located in open air at the harbor, about 1000 m from the PN tempera ture station (database Istituto Nazionale di Geofisica e Vulcanologia, Sezione di Palermo, courtesy of Paolo Madonia); ii) a seismic station maintained by the INGV from which the daily number of seismic events can be counted (Cannata et al, 2012); iii) a UV scanning DOAS MARK1 allowing daily estimations of the total SO 2 flux from the volcano (see an extended description in Vita et al, 2012); and iv) a WEST Systems CO 2 flux meter with an automated accumulation chamber providing daily estimate of the diffuse CO 2 flux at the summit area (see an extend ed description in Inguaggiato et al, 2012b) coupled with an open air thermometer. Note that the geochemical data were not corrected from the atmospheric conditions that may influence the observations (Viveiros et al, 2008), and that the reported seismic data represent the daily number of events and short lived interruptions may have caused some values underestimations.…”
Section: La Fossa DI Vulcanomentioning
confidence: 99%
“…Small perturbations temporarily increasing the pore pressure can modify the effective normal stress and trigger seismicity. This phenomenon and other fracturing processes (due to alteration of rock to secondary minerals by reducing the shear stress required to initiate fracturing and/or increases in temperatures in the rock and consequent rock fracturing) are also able to enhance the rock's vertical permeability, thus favoring the rise of fluids (Cannata et al, 2012, and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…We compared seismic data with our results, because seismic swarms suggest the disruption of the hydrothermal system, an increase of the permeability inside the edifice, and consequently an increase of hot fluids flow toward the surface (Cannata et al, 2012;Milluzzo et al, 2010).…”
Section: Application Site and Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…During inter-eruptive periods, the thermal emissions by hydrothermal fluids, the emission of steam through the fumaroles and even the diffuse heat release from the ground are a significant part of the total energy released by the volcano. This slow and restless energy release is, in the long term, comparable to the seismic release of volcano-tectonic origin [6][7][8][9][10][11]. For many years, the amount of convective energy released on the surface of the Island of Vulcano has been estimated by direct samplings and measurements of the fumaroles of La Fossa cone [7,12], and the exhaling temperatures and the steam flows in some sample points have been measured.…”
Section: Introductionmentioning
confidence: 98%